AMP-kinase α2 subunit gene PRKAA2 variants are associated with total cholesterol, low-density lipoprotein-cholesterol and high-density lipoprotein-cholesterol in normal women. Issue 12 (26th June 2006) - Spencer-Jones, N J; Ge, D; Snieder, H; Perks, U; Swaminathan, R; Spector, T D; Carter, N D; O'Dell, S D
Abstract : Background: 5′-AMP-activated protein kinase (AMPK) inactivates critial ensymes in fatty acid and cholesterol synthesis. We hypothesised that the serum lipid profile may be influenced by genetic variation in the AMPK catalytic α2 subunit. Method: We examined association of 5 tagging SNPs (tSNPs) in the PRKAA2 gene with serum lipids in 2777 normal Caucasian females (mean age 47.4±12.5 years). Results: All tSNPs were associated with total- and LDL-cholesterol, (p<0.001 to 0.034), explaining variances of 0.13–0.59% and 0.11–0.55% respectively. One haplotype (frequency 34.7%) showed lower total- and LDL-cholesterol compared with the most common haplotype (frequency 45.7%) (p≤0.001), explaining 0.78% of total- and 0.75% of LDL-cholesterol. Another haplotype (frequency 10.5%) was significantly associated with lower HDL-cholesterol (p = 0.005), explaining 0.59% of variance. Conclusions: PRKAA2 gene variants are significantly associated with serum lipoproteins in a large sample of normal female Caucasians.